The Role of Ambidextrous Leadership and Self-Serving Bias in Enhancing Organizational Agility through Psychological Safety as a Mediating Variable in Non-Formal Education - Intan, Lusi Reni; Junengsih, Junengsih; Yosminaldi, Yosminaldi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Rapid environmental changes require organizations, including education and training institutions, to develop high adaptive capabilities, commonly referred to as organizational agility. This study aims to examine the role of ambidextrous leadership and self-serving bias in enhancing organizational agility through psychological safety as the mediating variable in non-formal education. A quantitative research design was employed using a survey method involving 108 employees of Build Better Communication, a non-formal education. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that ambidextrous leadership has a positive and significant effect on organizational agility (β = 0.394; p < 0.05) and psychological safety (β = 0.568; p < 0.05). Psychological safety also has a positive and significant effect on organizational agility (β = 0.335; p < 0.05). Self-serving bias has no significant direct effect on organizational agility (β = 0.028; p > 0.05), but it significantly influences psychological safety (β = 0.245; p < 0.05). Furthermore, psychological safety partially mediates the relationship between ambidextrous leadership and organizational agility (β = 0.190; p < 0.05) and fully mediates the relationship between self-serving bias and organizational agility (β = 0.082; p < 0.05). The R-square values of 0.412 for Psychological Safety and 0.433 for Organizational Agility indicate a moderate explanatory power of the model. These findings highlight the critical role of ambidextrous leadership and psychological safety in enhancing organizational agility and emphasize psychological safety as a key psychological mechanism linking leadership behavior and cognitive bias to organizational adaptability.